Implementation of Ecoprint Media Pounding Technique to Improve Creativity of 5-6 Year Old Children at Paud Pahlawan - Fitriyah, Ani; Mediyana, Mediyana; Pusparini, Dewi (STIT Attaqwa, 2025)
This study aims to examine the implementation of ecoprint media using the pounding technique as an effort to foster creativity in children aged 5–6 years at PAUD Pahlawan Panaan. The background of this research is the limited variation in learning media which affects the development of children's creativity. Ecoprint with pounding technique is a method of natural coloring that utilizes leaves and flowers by transferring pigments onto fabric through a pounding process. This activity provides opportunities for children to explore, create patterns, and express ideas using materials from their surroundings. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The results showed that the application of ecoprint allowed children to demonstrate original thinking, increased imagination, and confidence in expressing their ideas through artwork. The activity also stimulated fine and gross motor skills, collaborative behavior, and environmental awareness. Therefore, ecoprint pounding technique serves not only as an artistic tool, but also as an effective educational medium to support holistic child development.